2014
DOI: 10.1039/c4mb00253a
|View full text |Cite
|
Sign up to set email alerts
|

An integrated molecular dynamics, principal component analysis and residue interaction network approach reveals the impact of M184V mutation on HIV reverse transcriptase resistance to lamivudine

Abstract: The emergence of different drug resistant strains of HIV-1 reverse transcriptase (HIV RT) remains of prime interest in relation to viral pathogenesis as well as drug development. Amongst those mutations, M184V was found to cause a complete loss of ligand fitness. In this study, we report the first account of the molecular impact of M184V mutation on HIV RT resistance to 3TC (lamivudine) using an integrated computational approach. This involved molecular dynamics simulation, binding free energy analysis, princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…After the docking of the wild-type MTHFR-FAD complex, the Alanine 222 residue was mutated to valine using the graphical user interface (GUI) of Chimera (Pettersen et al, 2004), in order to generate the mutated variant. Both the wild and mutated (Ala222Val) MTHFR-FAD complexes were subjected to an all-atom molecular dynamics simulation using the previously reported parameters provided by Bhakat, Martin, and Soliman (2014) and Karubiu, Bhakat, and Soliman (2014). During molecular dynamics simulation, the effect of in silico mutations was monitored by performing different postdynamics analyses as described by Bhakat et al (2014).…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…After the docking of the wild-type MTHFR-FAD complex, the Alanine 222 residue was mutated to valine using the graphical user interface (GUI) of Chimera (Pettersen et al, 2004), in order to generate the mutated variant. Both the wild and mutated (Ala222Val) MTHFR-FAD complexes were subjected to an all-atom molecular dynamics simulation using the previously reported parameters provided by Bhakat, Martin, and Soliman (2014) and Karubiu, Bhakat, and Soliman (2014). During molecular dynamics simulation, the effect of in silico mutations was monitored by performing different postdynamics analyses as described by Bhakat et al (2014).…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Principle component analysis (PCA) is extensively used to effortlessly examine and identify data generated from MD simulations to highpoint principal modes accountable for changes in conformation [11]. The PTRAJ and CPPTRAJ modules were used in performing PCA C-alpha atoms [48] integrated with Amber 14 [13] The plots analysis showing the central conformational motions descriptive of each structure were created using Origin data analyses programme (www.originlab.com).…”
Section: Principle Component Analysis (Pca)mentioning
confidence: 99%
“…It has also been reported that the nucleotide binding site situated at the CTD is more favorable to guanosine-5 0 -triphosphate (GTP) over ATP, which would possibly enhance the selectivity of the new inhibitors against this site [9,17,59]. Herein we focus on the C-terminal dimerization inhibitors as this is the vital domain for the biological activity of Hsp90 [11].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations